Weed flora shifts and specialisation in winter oilseed rape in France. (25th May 2015) - Fried, G; Chauvel, B; Reboud, X; Lutman, Peter
Summary Temporally repeated data sets can provide useful information about the management practices governing changes in the arable weed flora. This study aimed (i) to investigate changes in the most common weed species in winter oilseed rape crops in France between the 1970s and the 2000s and (ii) to pinpoint the main plant biological traits and associated management practices underlying the development of a specific weed flora in this crop. We compared two large‐scale surveys covering France in the 1970s and the 2000s, the later survey including several floristic samplings, on two dates, and both herbicide‐free control and treated plots. This last survey aimed to identify the species best able to maintain high densities over a growing season of oilseed rape. Since the 1970s, the frequency of two‐thirds (69%) of the 26 most common species has changed, spectacularly in some cases, with several species once considered rare becoming very common (e.g. Geranium dissectum) and, conversely, some formerly common species becoming rarer (e.g. Stellaria media). Our results indicated a general strong increase in specialist weeds of oilseed rape. Weed species success was favoured by tolerance to oilseed rape herbicides and germination synchronous with the crop. The proportion of specialist oilseed rape weed species tended to increase with herbicide treatment intensity and to decrease with increases in the proportion of spring‐sown crops in the rotation. Changes to the rotation may therefore constitute an additional or alternative means of controlling some weeds well adapted to oilseed rape crops.